A-site deficiency improved the thermoelectric performance of high-entropy perovskite manganite-based ceramics. Issue 41 (5th October 2022) - Shi, Zongmo; Zhang, Junzhan; Wei, Jian; Hou, Xing; Cao, Shuyao; Tong, Sijie; Liu, Shangyi; Li, Xueting; Zhang, Ying
Abstract : The thermoelectric properties of perovskite CaMnO3 with A-site defects were synergistically optimized and the lowest κ t value of 0.94 W m −1 K −1 was found at 800 °C. Abstract : Perovskite-type manganite-based ceramics are a promising thermoelectric material at high temperature, while their poor electrical resistivity and thermal conductivity restrict their application in thermoelectricity generators. Entropy engineering can optimize the thermoelectric performance in both electron transport and phonon scattering. RE0.2 Ca0.2 Sr0.2 Ba0.2 Y0.2 MnO3 (RE = La, Nd, Ho, Lu) ceramics were prepared by using a solid state method. It is clearly confirmed that a high-entropy perovskite-type solid solution with some metallic oxides was obtained and all the A-site elements were dispersed homogeneously. A-site deficiency induced lattice disorders, stacking faults and sparse dislocation, were formed enhancing phonon scattering. A minimum total thermal conductivity of 0.94 W m −1 K −1 was obtained at 800 °C. With the increase of measured temperatures, the power factors and ZT values increased first and then decreased. The maximum power factor value of 25.3 μW m −1 K −2 was achieved at 600 °C for the La0.2 Ca0.2 Sr0.2 Ba0.2 Y0.2 MnO3 sample. This work suggests that the strategy of high-entropy engineering paves a novel way for synergistically optimizing the thermoelectric performance of oxide ceramics.